A study of selected themes of protest in Zakes Mda's post-apartheid fiction - Hoveka, Dineo Ida (University of Limpopo, 2009)
This dissertation examines elements of protest in four of Zakes Mda’s novels, namely, Ways of Dying (1995a), She Plays with the Darkness (1995b), The Heart of Redness (2000), and The Madonna of Excelsior (2002). The elements of protest that are identified and investigated in this study are abuse, betrayal, discrimination, and violence. This study also shows that these elements of protest that are investigated are a result of a lack of integrity and social accountability on the part of government, the civil service, and individuals themselves. In addition, this dissertation reveals the extent to which social injustices negatively influence the thinking and behaviour of the general South African society and thwart the aspirations of ordinary people. Finally, suggestions to curb abuse, betrayal, and discrimination are made.
Thesis (M.A. (English Studies)) --University of Limpopo, 2009
Keywords: Themes of protest; Discrimination; Abuse; Betrayal; Apartheid; Protest literature -- South Africa